Evaluation of some mechanical properties of dental alginate impression materials after fluoride addition - Hummud, israa (Iraqi National Journal of Nursing Specialties, 2012)
Objective:Fluorid-containing dental alginate impression materials can exert a considerable reduction inenamel solubility. The objective was to evaluate the effect of fluoride addition on the setting time andcompressive strength of alginate impression materials.Methodology: 60 samples were constructed from alginate impression material (30 samples for settingtime test and 30 samples for compressive strength test).Specimens of each test divided into threesubgroup. Group A: 10 specimens of alginate were mixed with distilled water [control], Group B: 10specimens of alginate were mixed with100-ppm fluoride and Group C:10 specimens of alginate weremixed with 2%Naf.Results: the result of setting time test showed that addition of 2% Naf to alginate impression materialswere delayed the setting reaction while the results of compressive strength test showed that high meanvalues were obtained from control group while group mixed with 2%Naf had lower compressivestrength.Recommendation: it can be concluded that addition of 100-ppm fluoride were affect on theproperties of alginate impression materials while addition of 2% Naf was deteriorated the properties ofalginate impression materials. So recommends the effect of fluoride addition in other concentration